2022
DOI: 10.3390/jpm12060993
|View full text |Cite
|
Sign up to set email alerts
|

Vav1 Selectively Down-Regulates Akt2 through miR-29b in Certain Breast Tumors with Triple Negative Phenotype

Abstract: Triple negative breast cancer (TNBC) represents the most aggressive breast tumor, showing a high intrinsic variability in terms of both histopathological features and response to therapies. Blocking the Akt signaling pathway is a well-studied approach in the treatment of aggressive breast tumors. The high homology among the Akt isoforms and their distinct, and possibly opposite, oncogenic functions made it difficult to develop effective drugs. Here we investigated the role of Vav1 as a potential down-regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…MiR‐29b has been demonstrated to suppress tumor growth by targeting the AKT2 isoform. 29 Our study found upregulation of AKT1 and AKT3, which are involved in the signaling pathway of PI3K, and previous studies have demonstrated overactivation of the PI3K pathway in breast cancer. The enhanced mTOR expression, induced by miR‐29b and miR‐497, may result from AKT overexpression and phosphorylation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…MiR‐29b has been demonstrated to suppress tumor growth by targeting the AKT2 isoform. 29 Our study found upregulation of AKT1 and AKT3, which are involved in the signaling pathway of PI3K, and previous studies have demonstrated overactivation of the PI3K pathway in breast cancer. The enhanced mTOR expression, induced by miR‐29b and miR‐497, may result from AKT overexpression and phosphorylation.…”
Section: Discussionsupporting
confidence: 83%
“…Further evidence of LINC01405's ability to act as a scavenger was provided when we observed a significant rise in the expression of essential target genes for both miRNAs. MiR‐29b has been demonstrated to suppress tumor growth by targeting the AKT2 isoform 29 . Our study found upregulation of AKT1 and AKT3, which are involved in the signaling pathway of PI3K, and previous studies have demonstrated overactivation of the PI3K pathway in breast cancer.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, the up-regulation of miR-29b reduces cell proliferation and induces the apoptosis of MCF7 cells by regulating the expression of STAT3 [ 54 ]. It has been recently demonstrated that, in certain molecular subtypes of triple-negative breast breast tumor cells, miR-29b-3p down-modulates Akt2, a member of the Akt family mainly involved in migration and metastasis of breast cancer, and prevents the in vivo lung colonization of MDA-MB-231 cells [ 73 ].…”
Section: Roles Of Mir-29b In Breast Cancermentioning
confidence: 99%